The power of creativity and the power of the city - the functioning of labour markets and its role for urban location in the restructuring of German advertising - Joachim Thiel (European Regional Science Association (ERSA), 2002)
Urban socio-economic theory today strongly focuses on the role of labour markets in shaping the structure of the urban economy and society. Particularly the strong polarisation of the urban society is often explained through the polarised structure of post-industrial service labour markets. Yet this theoretical focus, visible in a whole flood of literature, tends to disarticulate with the small number of studies which empirically attempt to unravel the structure and functioning of particular labour markets in cities. The present paper aims at filling this gap by providing insights into the predominantly urban and especially post-industrial labour market of advertising. At the same time it attempts to highlight the nexus between its structure and functioning and the spatial structure of the economic activity by examining the role of labour markets for the spatial restructuring of the German advertising industry. After giving a brief critical overview of the role of labour markets in contemporary urban theory, the restructuring of German advertising is portrayed in a more descriptive way, presenting employment data from the last twenty years. In a second empirical step a more profound qualitative approach to the sector is taken focusing on the way how different agency types attempt and succeed to manage the frequently conflicting interests of both their clients and their labour force. The paper concludes by launching two key arguments: first, it will be decisive for understanding future urban economies to get insights in just these labour markets of 'classic' post-industrial activities and, second, to understand them one has to seriously consider the way how they interact with the social relations the labour market actors are embedded in.
Keywords: 330